2021
DOI: 10.1021/acsestengg.1c00122
|View full text |Cite
|
Sign up to set email alerts
|

Application of Heterojunction Ni–Sb–SnO2 Anodes for Electrochemical Water Treatment

Abstract: Electrochemical oxidation can be used for decentralized wastewater treatment without the addition of chemicals. Antimony-doped tin oxide (Sb-SnO 2 : AT) provides a catalytic anode coating that is easily prepared at a relatively low cost. However, there is the potential of Sb leaching during use. To overcome this problem, a heterojunction anode is developed that uses an AT oxide layer as an ohmic contact and a nickel-doped AT oxide layer (NAT) with a substantially lower Sb content as an outer catalytic layer (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 49 publications
1
55
0
Order By: Relevance
“…Electrochemical impedance spectroscopy (EIS) measurement was performed in the electrolyte containing 120 mM K 3 Fe(CN) 6 , 120 mM K 3 Fe(CN) 6 , and 330 mM KCl over the frequency range of 0.1 Hz to 100 kHz with a 10 mV sine wave. 23 In the study of lake water treatment, chlorophyll- a samples were filtered, extracted, and measured by a fluorometer (TD-700, Turner Designs) according to the Welschmeyer method. 24 The MC-LR was measured by a ultra-high-performance liquid chromatography (UPLC) system coupled with a triple-stage quadrupole mass spectrometer (Thermo Scientific, Vanquish-TSQ ALTIS) equipped with a Phenomenex Luna Omega PS C18 column (1.6 μm, 100 × 2.1 mm 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrochemical impedance spectroscopy (EIS) measurement was performed in the electrolyte containing 120 mM K 3 Fe(CN) 6 , 120 mM K 3 Fe(CN) 6 , and 330 mM KCl over the frequency range of 0.1 Hz to 100 kHz with a 10 mV sine wave. 23 In the study of lake water treatment, chlorophyll- a samples were filtered, extracted, and measured by a fluorometer (TD-700, Turner Designs) according to the Welschmeyer method. 24 The MC-LR was measured by a ultra-high-performance liquid chromatography (UPLC) system coupled with a triple-stage quadrupole mass spectrometer (Thermo Scientific, Vanquish-TSQ ALTIS) equipped with a Phenomenex Luna Omega PS C18 column (1.6 μm, 100 × 2.1 mm 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Absorbance at 400 nm was used to quantify [H 2 O 2 ]. Electrochemical impedance spectroscopy (EIS) measurement was performed in the electrolyte containing 120 mM K 3 Fe­(CN) 6 , 120 mM K 3 Fe­(CN) 6 , and 330 mM KCl over the frequency range of 0.1 Hz to 100 kHz with a 10 mV sine wave . In the study of lake water treatment, chlorophyll- a samples were filtered, extracted, and measured by a fluorometer (TD-700, Turner Designs) according to the Welschmeyer method .…”
Section: Methodsmentioning
confidence: 99%
“…to reach electrode surface was characterized by the limitingcurrent method using Fe(CN) 6 3− /Fe(CN) 6 4− as the redox pair (Figure S2). 32,35 The k m values increase with increasing flow rate (Figure 2d) due to the enhanced convective flow. The k m at the flow rate of 1.5 L/min (flux: 7377 L/(m 2 h)) is 1.16 × 10 −3 cm/ s, commensurate with those of the best-performing Ti 4 O 7 ceramics membrane electrodes ((1−1.4) × 10 −3 cm/s).…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…Details are summarized in Text S1. Trihalomethanes (THMs) and haloacetic acids (HAAs) were extracted following EPA methods 551.1 and 552.2 , and then analyzed by gas chromatography with electron capture detection (GC-ECD) (Agilent 7890 GC-Micro ECD) with a 30 m Rxi-5 ms column (0.25 mm i.d., 0.25 μm film thickness, Restek) …”
Section: Methodsmentioning
confidence: 94%
“…A subsequent study is warranted for NSS/SiO x (with cutting-edge OZER efficiency as herein demonstrated), to tackle the effects of wastewater compositions (target pollutants, electrolyte pH, and redox active anions among others) and operational conditions (applied current or cell voltage) on the OZER mediated water treatment efficiency. Some critical points need to be addressed more carefully for practical applications in real wastewater treatment, such as (i) leaching of metal ions from an electrocatalyst under anodization, (ii) generation of toxic halogenated byproducts including bromate, N -nitrosamine, and organoiodine compounds among others, and (iii) mechanisms of pollutant degradation by the OZER . In order to deal with O 3 -resistant pollutants, significant process intensification is expected in combination with UV irradiation or the H 2 O 2 evolution cathode to activate dissolved O 3 into free •OH.…”
Section: Results and Discussionmentioning
confidence: 99%